EXPERIMENTS ON δ34S MIXING BETWEEN ORGANIC AND INORGANIC SULFUR SPECIES DURING THERMAL MATURATION - Amrani A.; Said-Ahamed W.; Lewan M.D.; Aizenshtat Z. (My University, 2006)
Reduced sulfur species were studied to constrain isotopic exchange-mixing with synthetic polysulfide cross-linked macromolecules (PCLM), model sulfur containing molecules and natural sulfur-rich kerogen, asphalt and oil of the Dead Sea area. PCLM represents protokerogens that are rich in sulfur and thermally unstable. Mixing rates of PCLM with HS-(aq) (added as (NH4)2S(aq)) at low to moderate temperatures (50-200 °C) are rapid. Elemental sulfur and H2S(gas) fully mix isotopes with PCLM during pyrolysis conditions at 200 °C. During these reactions significant structural changes of the PCLM occur to form polysulfide dimers, thiolanes and thiophenes. As pyrolysis temperatures or reaction times increase, the PCLM thermal products are transformed to more aromatic sulfur compounds. Isotopic mixing rates increase with increasing pyrolysis temperature and time. Polysulfide bonds (S-S) in the PCLM are responsible for most of these structural and isotopic changes because of their low stability. Conversely, sulfur isotope mixing does not occur between dibenzothiophene (aromatic S) or hexadecanthiol (C-SH) and HS-(aq) at 200 °C after 48 h. This shows that rates of sulfur isotope mixing are strongly dependent on the functionality of the sulfur in the organic matter. The order of isotopic mixing rates for organic matter is kerogen > asphalt > oil, which is inverse to their sulfur thermal stability. Asphalt and oil with more refractory sulfur show significantly lower isotopes mixing rates than the kerogen with more labile sulfur. Based on the findings of the present study we suggest that sulfur isotopes mixing can occur from early diagenesis into catagenesis and result in isotopic homogenization of the inorganic and organic reduced sulfur pools. ? 2006 Elsevier Inc. All rights reserved.